A longitudinal micro-foundational investigation into ambidextrous practices in an international alliance context–A case of a biopharma EMNE. Issue 1 (February 2021) - Pereira, Vijay; Patnaik, Swetketu; Temouri, Yama; Tarba, Shlomo; Malik, Ashish; Bustinza, Oscar
Abstract: This paper explores the development of an ambidextrous context in a rapidly growing emerging market multinational (EMNE), thus unbundling cultural and structural complexities. We use the micro-foundational lens of ambidexterity to explore and identify different processes, structures and mechanisms that underpin the development of ambidextrous practices in the EMNE. We adopt a longitudinal case study design to trace the evolution of the EMNE, which during the initial phases of its existence focused on supplying industrial enzymes and refined its technical base. In subsequent years, it exploited its technical base to emerge as a full-fledged biopharmaceutical EMNE and adopted strategic partnerships with international companies to explore new knowledge. Our novel and rich research context also provides us with insights on how this EMNE exploited its technological knowledge, whilst utilizing strategic alliances to simultaneously engage in exploratory activities. Through the micro-foundational lens of ambidexterity, we uncover the critical role played by its leadership in addressing paradoxical tensions for simultaneously managing exploitation and exploration in an international strategic alliance context.